Lessons of the Financial Crisis for Future Regulation of Financial Institutions and Markets and for Liquidity Management. (Policy Papers; Policy Paper ;, 2009)
This paper seeks to draw lessons for financial sector regulation and supervision and central bank liquidity management from the ongoing crisis, focusing principally on implications for the future rather than on immediate crisis management policies. Inadequacies in macroeconomic policies and the design of the international financial architecture exposed in the crisis will also have to be addressed to make the suggested changes in the regulatory framework effective.